Co-production of lactic acid and ethanol using rhizopus sp. From hydrolyzed inedible cassava starch and leaves - Azmi, Azlin Suhaida; Yusuf, Nurlisa; Jimat, Dzun Noraini; Mohamad Puad, Noor Illi (Kulliyah of Engineering, International Islamic University Malaysia (IIUM), 2016)
Production of lactic acid and ethanol from inedible cassava starch and leaves was investigated. Prior to fermentation, hydrolysis of the starch and leaves was conducted. Hydrolysis was optimized by manipulating at three levels each four particular factors, namely acid concentration, starch concentration, temperature, and reaction time. Maximum glucose yield of 0.96 g/g was obtained when 2.5% (w/v) of cassava leaves with 2.5% (w/v) of starch was hydrolyzed using 0.20 M nitric acid at 160 oC of temperature for 10 min. The potential of hydrolyzed cassava starch and leaves was then investigated for lactic acid production using fungal Rhizopus sp. The fermentation process was then conducted in a shake flask by varying four factors at three levels each. Maximum lactic acid and ethanol yields of 0.95 g/g and 0.52 g/g, respectively, were achieved at different optimum conditions. Lactic acid production was found to be linked to a decrease in ethanol production. Design Expert v6.0.8 was used to aid in the design of the experiment using Taguchi’s methodology.